Flexible friction nano-generator material based on silk fabric and Ecoflex and preparation method and application of flexible friction nano-generator material
Through the chemical/physical modification and nanotechnical processing of silk fabrics and Ecoflex, high-performance, low-cost, and degradable friction nanogenerators were prepared, solving the lack of flexibility, stability, cost and environmental protection of traditional friction nanogenerators. The problem of this achieves efficient collection of low-frequency mechanical energy and environmentally friendly applications.
Patent Information
- Application Number
- CN202411242514.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional friction nanogenerators have shortcomings in flexibility, performance stability, cost and environmental protection, which are difficult to meet the needs of wearable devices and other flexible applications, and the low-frequency mechanical energy harvesting efficiency is not good.
Silk fabric and biodegradable Ecoflex for chemical/physical modification, a positive and negative friction layer with electron donation and electron withdrawal ability was prepared, and ZnO nanofilm and Ag intercalated montmorillonite were grown through ALD technology to increase friction Output performance and stability of nanogenerators.
It significantly improves the flexibility, output performance and stability of friction nanogenerators, reduces production costs, and realizes efficient collection of low-frequency mechanical energy, and the material is degradable, which is in line with the trend of environmental protection.
Smart Images

Figure CN119210202A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of friction nanogenerators, and specifically relates to a flexible friction nanogenerator material based on silk fabric and Ecoflex, and a preparation method and application thereof. Background Art
[0002] As an innovative energy harvesting technology, triboelectric nanogenerator (TENG) successfully realizes the conversion of mechanical energy into electrical energy through the triboelectric effect and electrostatic induction principle. In recent years, it has shown great application potential in the fields of self-powered systems and flexible electronic devices. However, despite its many advantages, TENG still faces a series of challenges in its actual promotion, which are mainly due to the shortcomings of existing technologies.
[0003] Traditional TENG usually uses hard materials such as metals and polymers as friction layers. These materials have obvious defects in flexibility and are difficult to meet the needs of wearable devices and other flexible application scenarios. Hard materials are easily damaged when subjected to deformations such as bending and folding, which not only affects their service life but also reduces performance stability. In addition, the output performance of traditional TENG often fluctuates due to the limitations of the physical properties of the material itself and the preparation process, especially when used for a long time or when the environment changes, resulting in unstable power supply, which limits its application in devices that require continuous and stable power supply.
[0004] From an economic perspective, the preparation process of traditional TENG is complex and costly, involving a variety of expensive materials and precision processing technologies, which not only increases production costs, but also makes large-scale automated production difficult, limiting its commercialization and popularity. At the same time, most traditional TENGs are made of non-degradable materials, which imposes a long-term burden on the environment. With the improvement of environmental awareness, this issue has received increasing attention.
[0005] Furthermore, traditional TENG performs poorly in the collection efficiency of low-frequency mechanical energy, while the mechanical energy generated by many mechanical devices and human movements in practical applications is mostly in low-frequency form, which further limits the practical scope of TENG.
[0006] Therefore, it is particularly important to develop a new type of high-performance, low-cost, easy-to-prepare, lightweight, soft and degradable triboelectric nanogenerator. This invention is proposed in this context, aiming to overcome the shortcomings of the existing technology and promote the further development and application of TENG technology through innovative material selection and preparation process. Summary of the invention
[0007] The purpose of the present invention is to provide a fabric-based degradable friction nanogenerator, which is achieved by chemically / physically modifying natural cellulose silk fabric and biodegradable Ecoflex to give them electron-donating and electron-withdrawing abilities, and using them as positive and negative friction layers, respectively, to improve the output performance and stability of the friction nanogenerator.
[0008] The technical problem to be solved by the present invention is achieved through the following technical solutions: A method for preparing a flexible friction nanogenerator material based on silk fabric and Ecoflex, comprising the following steps: a. Preparation of positive friction materials: β-lactoglobulin was prepared into amyloid fibrils β-LGF; β-LGF was loaded on the surface of mulberry silk fabric SF through electrostatic and ionic bonding, and β-LGF was firmly bonded to the silk fabric through a cross-linking agent; ZnO of different thicknesses was grown on the surface of the composite fabric SF / β-LGF under the atomic deposition technology ALD to obtain the positive friction material SF / β-LGF / ZnO; b. Preparation of negative friction materials: Ag intercalated montmorillonite (Ag-MMT) was prepared by cation exchange method with Na intercalated montmorillonite (MMT) as raw material. Ag-MMT was dispersed in ethyl acetate and combined with a mixed solution of Ecoflex to prepare a negative friction material Ecoflex / Ag-MMT.
[0009] In step a, the preparation method of amyloid fibril β-LGF comprises: The β-lactoglobulin solution was subjected to refrigerated centrifugation and dialysis treatment under specific temperature and pH conditions; the treated solution was heated and stirred at 90 °C in an oil bath, and finally freeze-dried to obtain β-LGF powder.
[0010] In the preparation method of amyloid fibril β-LGF, the conditions of frozen centrifugation are: the solution is below 4°C and the pH is 4.6; the specific process of dialysis is: after collecting the supernatant and adjusting its pH value to 2, an 8 kDa dialysis membrane is selected and dialyzed with Milli-Q water at 4°C for 5 days.
[0011] In step a, the specific steps of loading β-LGF on mulberry silk fabric include: The β-LGF solution is mixed with the mulberry silk fabric and stirred to make the β-LGF adhere to the surface of the silk fabric; the β-LGF and the silk fabric are firmly combined by the cross-linking agent glutaraldehyde.
[0012] Before immersing the silk fabric in the prepared β-LGF solution, it needs to be pre-treated by immersing it in an ethanol solution; the specific method for firm bonding is: transferring the obtained amyloid fibril coated fabric to a 1% glutaraldehyde solution, so that the amyloid original fibers are attached to the surface of the fabric through cross-linking to form a coating, and then taking it out and drying it.
[0013] In step a, the specific steps of growing ZnO on the surface of the silk fabric include: Using an ALD reactor, ZnO precursor and reaction gas are introduced into the reaction chamber under specific conditions to cyclically deposit the ZnO coating on the surface of the silk fabric.
[0014] In step b, the preparation method of Ag intercalated montmorillonite Ag-MMT comprises: Na-MMT was mixed with AgNO3 solution, stirred at 70°C in the dark, centrifuged and dried to obtain Ag-MMT.
[0015] In step b, the preparation method of the Ecoflex / Ag-MMT composite membrane comprises: Mix the A component and the B component of Ecoflex in a mass ratio of 1:1; disperse Ag-MMT in ethyl acetate, add it to the Ecoflex mixed solution, and apply it into a thin film.
[0016] A flexible friction nanogenerator material based on silk fabric and Ecoflex prepared according to the above preparation method.
[0017] The prepared positive friction material SF / β-LGF / ZnO and negative friction material Ecoflex / Ag-MMT can be used to assemble flexible friction nanogenerator SE-TENG.
[0018] Compared with the traditional technology, the present invention has significant beneficial effects, which are specifically reflected in the following aspects: (1) Significantly improved flexibility: By using natural silk fabric and biodegradable Ecoflex, the friction nanogenerator of the present invention has significantly improved flexibility, making it more suitable for wearable devices and other flexible application scenarios.
[0019] (2) Enhanced output performance and stability: Chemical and physical modifications make silk fabrics have stronger electron-donating ability, while Ecoflex has stronger electron-absorbing ability. This innovative design significantly improves the electrical output performance of the friction nanogenerator. Experimental data show that compared with unmodified materials, the surface charge of the friction nanogenerator of the present invention can be increased by 10% to 150%, the short-circuit current can be increased by 30% to 300%, the open-circuit voltage can be increased by 10% to 150%, and the output performance is more stable.
[0020] (3) Reduced cost and easy mass production: The preparation method of the present invention has clear steps and simple operation, and the required raw materials are low-cost and easy to obtain. Such low cost and easy preparation characteristics make the present invention have the potential for large-scale production, which will help promote the commercialization of triboelectric nanogenerator technology.
[0021] (4) Environmentally friendly and degradable: Natural silk fabric and biodegradable Ecoflex are selected as the substrate, so that the friction nanogenerator of the present invention can be naturally degraded after use, reducing pollution to the environment and conforming to the current trend of sustainable development.
[0022] (5) High efficiency in collecting low-frequency mechanical energy: Aiming at the efficient collection of low-frequency mechanical energy, the present invention improves the energy collection efficiency under low-frequency conditions by optimizing the material structure and preparation process, making this technology have greater application potential in collecting low-frequency mechanical energy such as human body movement and mechanical vibration.
[0023] In summary, the present invention not only overcomes the shortcomings of traditional friction nanogenerators in terms of flexibility, performance stability, cost and environmental protection, but also injects new vitality into the development of the field of flexible wearable electronic devices by improving the efficiency of low-frequency mechanical energy collection. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic diagram of the structure of a friction nanogenerator suitable for a flexible wearable sensor of the present invention. Figure 2 AFM and TEM images of the amyloid fibrils (β-LGF) prepared in Example 2.
[0025] Figure 3 This is a SEM image of the composite silk fabric prepared in Example 2 with amyloid fibrils loaded and ZnO deposited thereon.
[0026] Figure 4 This is a diagram of the mechanical properties of the Ecoflex / Ag-MMT composite membrane prepared in Example 2.
[0027] Figure 5 This is the electrical output performance diagram of the friction nanogenerator (SE-TENG) prepared in Example 2, which is assembled with SF / β-LGF / ZnO composite silk fabric as the positive friction layer and Ecoflex / Ag-MMT composite film material as the negative friction layer. DETAILED DESCRIPTION
[0028] The following examples are given to illustrate the present invention in more detail. It is necessary to point out that the following examples cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by technical personnel skilled in the art to the above-mentioned invention contents to the present invention still fall within the scope of protection of the present invention.
[0029] The present invention provides a triboelectric nanogenerator type positive friction material SF / β-LGF / ZnO and a negative friction layer material Ecoflex / Ag-MMT suitable for a flexible sensor and a preparation method and application thereof, comprising the following steps: (1) Preparation of amyloid fibrils (β-LGF): β-lactoglobulin was used as the raw material, the pH was adjusted to its isoelectric point of 4.6, and the solution was centrifuged at 16000g for 45 minutes at 4°C. After collecting the supernatant and adjusting its pH to 2, an 8 kDa dialysis membrane was selected and dialyzed with Milli-Q water at 4°C for 5 days, and the bath was changed every day to remove ions from the solution. The solution was stirred and heated in an oil bath at 90°C for about 5 hours, and the final solution was freeze-dried to obtain β-LGF powder.
[0030] (2) Preparation of silk fabric loaded with amyloid fibrils (SF / β-LGF) composite fabric: The prepared amyloid fibrils were concentrated at 1 mg / mL -1 The concentration of β-LGF was ultrasonically dispersed in ultrapure water, the pH was adjusted to 2, a 3cm×3cm silk fabric was selected and immersed in the prepared β-LGF solution and slowly stirred for 48h, the fabric was taken out and rinsed with Milli-Q water and then dried, the above steps were repeated, and the obtained amyloid fibril coated fabric was transferred to a 1% glutaraldehyde solution, so that the amyloid original fibers were attached to the surface of the fabric through cross-linking to form a coating, and the fabric was taken out and dried in an oven for use.
[0031] (3) Preparation of silk fabric loaded with amyloid fibrils (SF / β-LGF) composite fabric and ZnO deposition (SF / β-LGF / ZnO) composite fabric: An ALD reactor was used to load ultra-thin ZnO nanofilms on the surface of silk fabrics. The process was to place the bare silk fabric in the reaction chamber and dry it at 90°C and about 0.05 Torr. DEZ was heated to 90°C to generate sufficient vapor pressure. H2O was kept at ambient temperature. High-purity nitrogen (N2, 99.999%) was used as a precursor carrier and purge gas. However, a complete ALD ZnO cycle consisted of two half cycles. In the first half of the cycle, the silk fabric was purged with nitrogen for 30 seconds. In the second half of the cycle, the precursor ZnO vapor entered the reaction chamber at a rate of 20sccm. Then SF was exposed to H2O and the reactants were purged with high-purity nitrogen. ZnO coatings were grown on the surface of silk fabrics through multiple cycles.
[0032] (4) Preparation of Ag intercalated montmorillonite: The Na-MMT powder was ultrasonically dispersed in 200 mL of deionized water, and then AgNO3 was dispersed in it. The mixture was stirred at 70 °C in the dark for 12 h (avoiding the presence of Ag). + The photoreduction to elemental Ag, which is further oxidized to Ag2O) ensures the dispersion and peeling of the MMT layer, as well as the bonding between the MMT layer and Ag. + The obtained product was centrifuged and washed three times with deionized water, and the product was collected and freeze-dried for later use.
[0033] (5) Preparation of Ecoflex / Ag-MMT composite membrane: Component A and component B of Ecoflex-30 were mixed at a ratio of 1:1, and the prepared Ag-MMT was dispersed in ethyl acetate and added to the Ecoflex mixed solution. The obtained Ecoflex / Ag-MMT mixed solution was scraped into a 0.3 mm film in a fume hood.
[0034] Preferably, the pH adjustment buffer is 1 M HCL.
[0035] Preferably, a quenching reaction is required in step (1), specifically, the β-lactoglobulin is heated at 90° C. for several hours and then taken out and immediately placed in an ice water bath.
[0036] Preferably, the 3 cm×3 cm undyed and unmodified white embryo mulberry silk (to avoid the influence of active groups in the surface coating) taken in step (2) needs to be immersed in an ethanol solution for ultrasonic pretreatment for 30 minutes.
[0037] Preferably, in step (3), both H2O and DEZ are gases, and the silk fabric is purged for different lengths of time.
[0038] Preferably, the Ag intercalated montmorillonite in step (4) needs to be freeze-dried in a dark environment and ground into fine powder after freeze-drying.
[0039] Preferably, in step (5), Ag-MMT is dispersed in ethyl acetate and film-formed, and the whole process is carried out in a fume hood, and the maximum ratio of the two is 2:3. If the ratio exceeds this, ethyl acetate will destroy the colloidal structure of Ecoflex, making it unable to gel well.
[0040] Example 1 β-lactoglobulin was used as the raw material, the pH was adjusted to its isoelectric point of 4.6, and the solution was centrifuged at 16000g for 45 minutes at 4°C. After collecting the supernatant and adjusting its pH to 2, an 8 kDa dialysis membrane was selected and dialyzed with Milli-Q water at 4°C for 5 days, and the bath was changed every day to remove ions from the solution. The solution was stirred and heated in an oil bath at 80°C for about 4 hours, and the final solution was freeze-dried to obtain β-LGF powder.
[0041] The prepared amyloid fibrils were concentrated at 1 mg / mL -1 The concentration of β-LGF was dispersed in ultrapure water, the pH was adjusted to 2, 3cm×3cm undyed and unmodified white embryo mulberry silk (to avoid the influence of active groups in the surface coating) was selected and immersed in an ethanol solution for pretreatment for 10 minutes, and then the silk fabric was immersed in the prepared β-LGF solution and slowly stirred. After taking it out, it was rinsed with Milli-Q water and dried. The above steps were repeated to transfer the obtained amyloid fibril coated fabric to a 1% glutaraldehyde solution, so that the amyloid original fibers were attached to the surface of the fabric through cross-linking to form a coating, and it was taken out and dried in an oven for use.
[0042] An ALD reactor was used to load ultra-thin ZnO nanofilms on the surface of silk fabrics. The process was to place the bare silk fabric in the reaction chamber and dry it at 90°C and about 0.05 Torr. DEZ was heated to 90°C to generate sufficient vapor pressure. H2O was kept at ambient temperature. High-purity nitrogen (N2, 99.999%) was used as a precursor carrier and purge gas. However, a complete ALD ZnO cycle consisted of two half cycles. In the first half of the cycle, the silk fabric was purged with nitrogen for 30 seconds. In the second half of the cycle, the precursor ZnO vapor entered the reaction chamber at a rate of 20sccm. Then SF was exposed to H2O and the reactants were purged with high-purity nitrogen. ZnO coatings were grown on the surface of silk fabrics through multiple cycles.
[0043] The Na-MMT powder was ultrasonically dispersed in 200 mL of deionized water, and then AgNO3 was dispersed in it. The mixture was stirred at 60 °C in the dark for 12 h (avoiding the presence of Ag). + The photoreduction to elemental Ag, which is further oxidized to Ag2O) ensures the dispersion and peeling of the MMT layer, as well as the bonding between the MMT layer and Ag. + The obtained product was centrifuged and washed three times with deionized water, and the product was collected and freeze-dried for later use.
[0044] Mix component A and component B of Ecoflex-30 in a ratio of 1:1, disperse the prepared Ag-MMT in ethyl acetate in a ratio of 1:1, and add the mixture to the Ecoflex mixed solution. Scrape the obtained Ecoflex / Ag-MMT mixed solution into a 0.3 mm film in a fume hood.
[0045] Example 2 β-lactoglobulin was used as the raw material, the pH was adjusted to its isoelectric point of 4.6, and the solution was centrifuged at 16000g for 45 minutes at 4°C. After collecting the supernatant and adjusting its pH to 2, an 8 kDa dialysis membrane was selected and dialyzed with Milli-Q water at 4°C for 5 days, and the bath was changed every day to remove ions from the solution. The solution was stirred and heated in an oil bath at 90°C for about 5 hours, and the final solution was freeze-dried to obtain β-LGF powder.
[0046] The prepared amyloid fibrils were concentrated at 1 mg / mL -1 The concentration of β-LGF was dispersed in ultrapure water, the pH was adjusted to 2, 3cm×3cm undyed and unmodified white embryo mulberry silk (to avoid the influence of active groups in the surface coating) was selected and immersed in an ethanol solution for pretreatment for 30 minutes, and then the silk fabric was immersed in the prepared β-LGF solution and slowly stirred. After taking it out, it was rinsed with Milli-Q water and dried. The above steps were repeated, and the obtained amyloid fibril coated fabric was transferred to a 1% glutaraldehyde solution, so that the amyloid original fibers were attached to the surface of the fabric through cross-linking to form a coating. After taking it out, it was dried in an oven for standby use.
[0047] An ALD reactor was used to load ultra-thin ZnO nanofilms on the surface of silk fabrics. The process was to place the bare silk fabric in the reaction chamber and dry it at 90°C and about 0.05 Torr. DEZ was heated to 90°C to generate sufficient vapor pressure. H2O was kept at ambient temperature. High-purity nitrogen (N2, 99.999%) was used as a precursor carrier and purge gas. However, a complete ALD ZnO cycle consisted of two half cycles. In the first half of the cycle, the silk fabric was purged with nitrogen for 30 seconds. In the second half of the cycle, the precursor ZnO vapor entered the reaction chamber at a rate of 20sccm. Then SF was exposed to H2O and the reactants were purged with high-purity nitrogen. ZnO coatings were grown on the surface of silk fabrics through multiple cycles.
[0048] The Na-MMT powder was ultrasonically dispersed in 200 mL of deionized water, and then AgNO3 was dispersed in it. The mixture was stirred at 70 °C in the dark for 12 h (avoiding the presence of Ag). + The product was photoreduced to elemental Ag and further oxidized to Ag2O) to ensure the dispersion and exfoliation of the MMT layer and the exchange of Ag+ between the MMT layers. The obtained product was centrifuged and washed with deionized water for three times. The product was collected and freeze-dried for later use.
[0049] Mix component A and component B of Ecoflex-30 in a ratio of 1:1, disperse the prepared Ag-MMT in ethyl acetate in a ratio of 2:3, and add the mixture to the Ecoflex mixed solution. Scrape the obtained Ecoflex / Ag-MMT mixed solution into a 0.3 mm film in a fume hood.
[0050] Example 3 β-lactoglobulin was used as the raw material, the pH was adjusted to its isoelectric point of 4.6, and the solution was centrifuged at 16000g for 45 minutes at 4°C. After collecting the supernatant and adjusting its pH to 2, an 8 kDa dialysis membrane was selected and dialyzed with Milli-Q water at 4°C for 5 days, and the bath was changed every day to remove ions from the solution. The solution was stirred and heated in an oil bath at 100°C for about 8 hours, and the final solution was freeze-dried to obtain β-LGF powder.
[0051] The prepared amyloid fibrils were concentrated at 1 mg / mL -1The concentration of β-LGF was dispersed in ultrapure water, the pH was adjusted to 2, 3cm×3cm undyed and unmodified white embryo mulberry silk (to avoid the influence of active groups in the surface coating) was selected and immersed in an ethanol solution for pretreatment for 60 minutes, and then the silk fabric was immersed in the prepared β-LGF solution and slowly stirred. After taking it out, it was rinsed with Milli-Q water and dried. The above steps were repeated, and the obtained amyloid fibril coated fabric was transferred to a 1% glutaraldehyde solution, so that the amyloid original fibers were attached to the surface of the fabric through cross-linking to form a coating, and it was taken out and dried in an oven for use.
[0052] An ALD reactor was used to load ultra-thin ZnO nanofilms on the surface of silk fabrics. The process was to place the bare silk fabric in the reaction chamber and dry it at 90°C and about 0.05 Torr. DEZ was heated to 90°C to generate sufficient vapor pressure. H2O was kept at ambient temperature. High-purity nitrogen (N2, 99.999%) was used as a precursor carrier and purge gas. However, a complete ALD ZnO cycle consisted of two half cycles. In the first half of the cycle, the silk fabric was purged with nitrogen for 30 seconds. In the second half of the cycle, the precursor ZnO vapor entered the reaction chamber at a rate of 20sccm. Then SF was exposed to H2O and the reactants were purged with high-purity nitrogen. ZnO coatings were grown on the surface of silk fabrics through multiple cycles.
[0053] The Na-MMT powder was ultrasonically dispersed in 200 mL of deionized water, and then AgNO3 was dispersed in it. The mixture was stirred at 80 °C in the dark for 12 h (avoiding the presence of Ag). + The product was photoreduced to elemental Ag and further oxidized to Ag2O) to ensure the dispersion and exfoliation of the MMT layer and the exchange of Ag+ between the MMT layers. The obtained product was centrifuged and washed with deionized water for three times. The product was collected and freeze-dried for later use.
[0054] Mix component A and component B of Ecoflex-30 in a ratio of 1:1, disperse the prepared Ag-MMT in ethyl acetate in a ratio of 1:2, and add the mixture to the Ecoflex mixed solution. Scrape the obtained Ecoflex / Ag-MMT mixed solution into a 0.3 mm film in a fume hood.
[0055] The technical effects of the present invention are further described below in conjunction with the accompanying drawings, wherein: Figure 1The structural schematic diagram of the flexible wearable friction nanogenerator (SE-TENG) prepared by the present invention is shown. The generator adopts a contact-separation design, which is mainly composed of a positive friction layer SF / β-LGF / ZnO composite silk fabric and a negative friction layer Ecoflex / Ag-MMT composite film. The positive friction layer is connected to the copper wire through a conductive fabric, and the negative friction layer is also connected to another copper wire through a conductive fabric. Degradable EP pearl cotton is used as an isolation layer between the two layers of friction material to ensure that the positive and negative electrodes do not directly contact during the contact and separation process, while maintaining a certain flexibility. The entire structure is encapsulated with a degradable cellulose antistatic tape to ensure the stability and durability of the generator. This design is not only simple in structure, but also easy to prepare, with good flexibility, stability and low-frequency mechanical energy collection function, and can effectively convert the collected low-frequency mechanical energy into electrical energy.
[0056] Figure 2 The AFM and TEM images of amyloid fibrils (β-LGF) prepared in Example 2 show that amyloid fibrils using β-lactoglobulin as raw material have been successfully prepared. The images clearly show the fibrous structure of β-LGF, verifying the successful self-assembly of β-lactoglobulin into amyloid fibrils under specific pH and temperature conditions. These fibers have uniform diameter and length, providing a good foundation for subsequent loading on the surface of silk fabrics, helping to improve the surface roughness and charge density of silk fabrics, and thus enhancing the electrical output performance of the friction nanogenerator.
[0057] Figure 3 This is a SEM image of the composite silk fabric prepared in Example 2 with amyloid fibrils attached and ZnO deposited. As can be seen from the figure, it can be clearly seen that the amyloid fibrils are evenly distributed on the surface of the silk fabric, and the deposited ZnO nanofilm repairs the uneven microscopic morphology caused by the fibers to a certain extent, making the surface of the composite silk fabric smoother. This structure not only retains the flexibility of the silk fabric, but also enhances its mechanical strength and UV resistance, which helps to improve the stability and service life of the friction nanogenerator.
[0058] Figure 4 This is a graph of the mechanical properties of the Ecoflex / Ag-MMT composite film prepared in Example 2. The data in the graph show that when the Ag-MMT addition is 6%, the stress of the composite film reaches the optimal state. This result shows that an appropriate amount of Ag-MMT filling can significantly improve the mechanical properties of Ecoflex, making it more suitable as a negative friction layer material for triboelectric nanogenerators. The enhanced mechanical properties help improve the stability and durability of the generator in complex application environments.
[0059] Figure 5The electrical output performance diagram of the friction nanogenerator (SE-TENG) prepared in Example 2, which is composed of SF / β-LGF / ZnO composite silk fabric as the positive friction layer and Ecoflex / Ag-MMT composite film material as the negative friction layer, shows that the open circuit voltage of the generator modified by the positive and negative electrodes can be increased by up to 150%, showing excellent electrical output performance. In addition, the generator can also effectively monitor the mechanical energy generated by some human body movements, verifying its wide application prospects in the field of flexible wearable electronic devices. These performance improvements are mainly attributed to the innovative material selection and optimized preparation process used in the present invention.
[0060] In summary, the present invention has successfully developed a high-performance, light and soft, excellent electrical output performance, good stability, low cost and degradable flexible wearable friction nanogenerator material. Through chemical and physical modification, natural silk fabric and biodegradable Ecoflex are respectively endowed with stronger electron donating and electron absorbing capabilities, which significantly improves the electrical output performance and stability of the generator. The experimental results show that the generator performs excellently in low-frequency mechanical energy collection, can effectively convert mechanical energy into electrical energy, and provides a new solution for the field of flexible wearable electronic devices. In addition, the preparation method of the present invention is simple, low-cost and easy to mass produce, has good environmental protection and application prospects, and lays a solid foundation for the further promotion and application of friction nanogenerator technology.
Claims
1. A method for preparing a flexible friction nanogenerator material based on silk fabric and Ecoflex, characterized in that: The following steps are involved: a. Preparation of positive friction materials: β-lactoglobulin was prepared into amyloid fibrils β-LGF; β-LGF was loaded on the surface of mulberry silk fabric SF through electrostatic and ionic bonding, and β-LGF was firmly bonded to the silk fabric through a cross-linking agent; ZnO of different thicknesses was grown on the surface of the composite fabric SF / β-LGF under the atomic deposition technology ALD to obtain the positive friction material SF / β-LGF / ZnO; b. Preparation of negative friction materials: Ag intercalated montmorillonite (Ag-MMT) was prepared by cation exchange method with Na intercalated montmorillonite (MMT) as raw material. Ag-MMT was dispersed in ethyl acetate and combined with a mixed solution of Ecoflex to prepare a negative friction material Ecoflex / Ag-MMT.
2. The preparation method according to claim 1, characterized in that: In step a, the preparation method of amyloid fibril β-LGF comprises: The β-lactoglobulin solution was subjected to refrigerated centrifugation and dialysis treatment under specific temperature and pH conditions; the treated solution was heated and stirred at 90 °C in an oil bath, and finally freeze-dried to obtain β-LGF powder.
3. The preparation method according to claim 2, characterized in that: In the preparation method of amyloid fibril β-LGF, the conditions of frozen centrifugation are: the solution is below 4°C and the pH is 4.6; the specific process of dialysis is: after collecting the supernatant and adjusting its pH value to 2, an 8 kDa dialysis membrane is selected and dialyzed with Milli-Q water at 4°C for 5 days.
4. The preparation method according to claim 1, characterized in that: In step a, the specific steps of loading β-LGF on mulberry silk fabric include: The β-LGF solution is mixed with the mulberry silk fabric and stirred to make the β-LGF adhere to the surface of the silk fabric; the β-LGF and the silk fabric are firmly combined by the cross-linking agent glutaraldehyde.
5. The preparation method according to claim 4, characterized in that: Before immersing the silk fabric in the prepared β-LGF solution, it needs to be pre-treated by immersing it in an ethanol solution; the specific method for firm bonding is: transferring the obtained amyloid fibril coated fabric to a 1% glutaraldehyde solution, so that the amyloid original fibers are attached to the surface of the fabric through cross-linking to form a coating, and then taking it out and drying it.
6. The preparation method according to claim 1, characterized in that: In step a, the specific steps of growing ZnO on the surface of the silk fabric include: Using an ALD reactor, ZnO precursor and reaction gas are introduced into the reaction chamber under specific conditions to cyclically deposit the ZnO coating on the surface of the silk fabric.
7. The preparation method according to claim 1, characterized in that: In step b, the preparation method of Ag intercalated montmorillonite Ag-MMT comprises: Na-MMT was mixed with AgNO3 solution, stirred at 70°C in the dark, centrifuged and dried to obtain Ag-MMT.
8. The preparation method according to claim 1, characterized in that: In step b, the preparation method of the Ecoflex / Ag-MMT composite membrane comprises: Mix the A component and the B component of Ecoflex in a mass ratio of 1:1; disperse Ag-MMT in ethyl acetate, add it to the Ecoflex mixed solution, and apply it into a thin film.
9. A flexible friction nanogenerator material based on silk fabric and Ecoflex prepared by the preparation method as claimed in claim 1.
10. An application of the flexible friction nanogenerator material based on silk fabric and Ecoflex in a fabric-based wearable friction nanogenerator as claimed in claim 9, characterized in that: The prepared positive friction material SF / β-LGF / ZnO and negative friction material Ecoflex / Ag-MMT can be used to assemble flexible friction nanogenerator SE-TENG.
Citation Information
Cited By
Preparation method of full-biomass-based friction nano-generator
CN121000088A